An online learning space facilitating supervision pedagogies in science - Picard, MY; Wilkinson, K; Wirthensohn, M (South African Journal of Higher Education, 2011)
Quality research supervision leading to timely completion and student satisfaction involves explicit pedagogy and effective communication. This article describes the development within an action research cycle of an online learning space designed to achieve these goals. The research ‘spirals’ involved interventions in the form of instructive resources scaffolding best practice and discussion starters facilitating quality interactions. These were evaluated by focus groups and surveys of supervisors, postgraduate coordinators and research students. The instructive resources were valued for their interactivity, conciseness, clarification of research issues, and development of confidence, while the discussion starters were valued for their access ease, unpacking of expectations, encouragement of independent reflection, and enhancement of confidence in supervision relationships. Although the framework and pedagogies for effective supervision in Science have been well described, this online learning space is the first to address the interaction between supervisors and research students and provide resources for facilitating supervision pedagogy.